2018
DOI: 10.1016/j.pec.2018.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating implementation of shared decision-making in the Netherlands: An exploratory investigation

Abstract: Stakeholders should connect nationwide initiatives to pool information, and make the healthcare system supportive of implementing SDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 43 publications
2
89
0
Order By: Relevance
“…Although option talk does seem to take place, the three projects also described lack of overview of all existing options for the specific patient groups, for example, regarding transmural care, rehabilitation, and primary care. This corresponds to previous findings in the Dutch context that clinicians perceive a lack of adequate (patient) information on available options.…”
Section: Forerunner Case Examples From the Netherlandssupporting
confidence: 89%
See 3 more Smart Citations
“…Although option talk does seem to take place, the three projects also described lack of overview of all existing options for the specific patient groups, for example, regarding transmural care, rehabilitation, and primary care. This corresponds to previous findings in the Dutch context that clinicians perceive a lack of adequate (patient) information on available options.…”
Section: Forerunner Case Examples From the Netherlandssupporting
confidence: 89%
“…In this training, attention should be devoted to the importance of SDM in delivering high value for patients, the employment of available PROMs and decision aids, and avoiding the silent misdiagnosis of patients' preferences and overtreatment . In general, it also seems important to clearly instruct what SDM entails, because previous studies suggest the concept is often unclear for clinicians …”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Because professionals in this study indicated that patients should take the initiative in discussing PROMs, it seems somewhat unlikely that PROMs information will actually be used for shared decision making, unless professionals will be explicitly instructed and trained in taking the initiative. In addition, initiatives to stimulate an active role of patients may be needed …”
Section: Discussionmentioning
confidence: 99%